2020
DOI: 10.1038/s41598-020-77069-z
|View full text |Cite
|
Sign up to set email alerts
|

Genomic selection for heterobothriosis resistance concurrent with body size in the tiger pufferfish, Takifugu rubripes

Abstract: Parasite resistance traits in aquaculture species often have moderate heritability, indicating the potential for genetic improvements by selective breeding. However, parasite resistance is often synonymous with an undesirable negative correlation with body size. In this study, we first tested the feasibility of genomic selection (GS) on resistance to heterobothriosis, caused by the monogenean parasite Heterobothrium okamotoi, which leads to huge economic losses in aquaculture of the tiger pufferfish Takifugu r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…In conclusion, our data revealed that GS is available for improvement of TW as is the case for SL and BW in selective breeding of the tiger pufferfish 22 . A medium size dataset of SNPs (4075 SNPs) is sufficient for accurate prediction, but the number of SNPs can be reduced to 1200 without much loss of accuracy.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In conclusion, our data revealed that GS is available for improvement of TW as is the case for SL and BW in selective breeding of the tiger pufferfish 22 . A medium size dataset of SNPs (4075 SNPs) is sufficient for accurate prediction, but the number of SNPs can be reduced to 1200 without much loss of accuracy.…”
Section: Discussionmentioning
confidence: 51%
“…Atlantic salmon ( Salmo salar ; length: 0.61, weight: 0.60) 29 , common carp ( Cyprinus carpio ; length: 0.33) 30 , Nile tilapia ( Oreochromis niloticus ; weight: 0.36) 31 , channel catfish ( Ictalurus punctatus ; weight: 0.34) 32 , large yellow croaker ( Larimichthys crocea ; length: 0.59, weight: 0.60, gonad weight: 0.37) 33 , 34 , yellowtail kingfish ( Seriola lalandi ; length: 0.43, weight: 0.47) 35 , and the tiger pufferfish (length: 0.41) 22 . Prediction accuracy was relatively high for all of the traits (prediction accuracy: 0.665‒0.792), but also within the range of previous studies: Atlantic salmon (weight: 0.70, length: 0.66) 29 , common carp (length: 0.71) 30 , Nile tilapia (weight: 0.60) 31 , channel catfish (weight: 0.37) 32 , large yellow croaker (length: 0.40, weight: 0.41) 33 , yellowtail kingfish (length: 0.67, weight: 0.69) 35 , and the tiger pufferfish (length: 0.73) 22 . The high heritability and prediction accuracy indicate that GS can be applied for selective breeding on TW in addition to SL and BW of the tiger pufferfish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GS predicts GEBVs using whole‐genome molecular markers for individuals from test populations with only genotype data and for individuals from reference populations with both phenotypes and genotype data. This technology has been implemented in increasing numbers of species and has led to successful rapid genetic improvement, especially for traits with low heritability and traits affected by complex and multiple minor loci 214–218 . After several years of exploring the GS algorithms, there have been multiple genomic prediction models, and these can be divided into three main categories: direct models such as GBLUP, indirect models such as Bayesian models and machine learning models such as random forests.…”
Section: Future Perspectives For Common Carp Genetic Improvementmentioning
confidence: 99%
“…This technology has been implemented in increasing numbers of species and has led to successful rapid genetic improvement, especially for traits with low heritability and traits affected by complex and multiple minor loci. [214][215][216][217][218] After several years of exploring the GS algorithms, there have been multiple genomic prediction models, and these can be divided into three main categories: direct models such as GBLUP, indirect models such as Bayesian models and machine learning models such as random forests. Which model is a better fit depends on their predictive abilities and correlations between the simulated and actual data sets.…”
Section: Apply Gs For Faster Genetic Improvementmentioning
confidence: 99%